Answer: First option.
Step-by-step explanation:
1. To solve this problem you can applly the quadratic formula, which is shown below:
![x=\frac{-b+/-\sqrt{b^{2}-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%2B%2F-%5Csqrt%7Bb%5E%7B2%7D-4ac%7D%7D%7B2a%7D)
2. The quadratic equation is:
![x^{2}-4x-9-29=0\\x^{2}-4x-38=0](https://tex.z-dn.net/?f=x%5E%7B2%7D-4x-9-29%3D0%5C%5Cx%5E%7B2%7D-4x-38%3D0)
3. Then:
a=1
b=-4
c=-38
4. Therefore, when you substitute these values into the quadratic formula, you obtain the following result:
![x=\frac{-(-4)+/-\sqrt{(-4)^{2}-4(1)(-38)}}{2(1)}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-%28-4%29%2B%2F-%5Csqrt%7B%28-4%29%5E%7B2%7D-4%281%29%28-38%29%7D%7D%7B2%281%29%7D)
x=2±√42
Answer:
The probability that they sit next to each other is 50%.
Step-by-step explanation:
Consider the provided information.
It is given that there are four seats within the row are first come, first served during boarding.
There are 4 seats and 2 customers (Karen and Georgia)
The total number of ways in which Karen and Georgia can sit is: ![^4C_2](https://tex.z-dn.net/?f=%5E4C_2)
Now if they will sit together, then consider Karen and Georgia as a single unit.
Thus, the number of ways in which they can sit together is: ![^3C_1](https://tex.z-dn.net/?f=%5E3C_1)
The required probability is:
![P=\frac{^3C_1}{^4C_2} \\\\P=\frac{3}{6}\\\\P=\frac{1}{2}](https://tex.z-dn.net/?f=P%3D%5Cfrac%7B%5E3C_1%7D%7B%5E4C_2%7D%20%5C%5C%5C%5CP%3D%5Cfrac%7B3%7D%7B6%7D%5C%5C%5C%5CP%3D%5Cfrac%7B1%7D%7B2%7D)
Hence, the probability that they sit next to each other is 50%.
Answer: brainliest please
Part 1) Option D
Part 2) Option C
Step-by-step explanation:
we know that
In a Rhombus
Opposite angles are congruent, and consecutive angles are supplementary. All sides are congruent by definition. The diagonals bisect the angles
Part 1) What is the measure of angle ?
-----> remember that the diagonals bisect the angles
Part 2) What is the measure of angle ?
Remember that
In a rhombus consecutive angles are supplementary
so
The measure of angle is equal to the measure of angle T divided by
Step-by-step explanation:
The heck, what math are you in?
you know that (0,3) is a point and (1,1) is another point.
so now you have to replace them in the follow equations.
i did that and the right answer is the first equation => y=-2x+3